Evaluating an owner‐to‐worker training intervention in California nail salons using personal air monitoring. Issue 10 (12th August 2018) - Quach, Thu; Von Behren, Julie; Nelson, David O.; Nguyen, Tuan N.; Tsoh, Janice; Le, Minhthu; Fu, Lisa; Beckman, Stella; Reynolds, Peggy
Abstract : Background: Chemicals in nail products have been linked to numerous health concerns. Methods: We recruited Vietnamese‐American nail salon owners and workers in California and randomized salons into an intervention or control group. Owners in the intervention group received training and then provided education to workers in their salons on best practices to reduce workplace chemical exposures. Methyl methacrylate (MMA), toluene, and total volatile organic compounds (TVOCs) were measured using personal air monitors worn by workers during the work‐shift. Results: We enrolled 77 salons (37 intervention and 40 control) and 200 workers. There was no significant intervention effect between the two groups. However, MMA and TVOCs were higher for workers who used gel polish and acrylic nails as well as in busy salons. Conclusions: Although the intervention did not show reductions in chemical levels, identifying worker tasks and salon characteristics that predict chemical levels can inform future interventions to reduce exposures.